1991
DOI: 10.1093/ptj/71.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Balance Changes in Hearing-Impaired Children

Abstract: This study compared balance skills of hearing-impaired children with those of hearing children in order to determine whether a deficit in balance exists in hearing-impaired children and to ascertain whether this deficit is age-related. Twenty-eight hearing-impaired subjects were chosen as a sample of convenience from the Pennsylvania School for the Deaf and placed into one of three age groups. Ten subjects were in the 4.5 to 6.5-year-old age group, 8 in the 8- to 10-year-old age group, and 10 in the 12.5 to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 11 publications
5
48
0
4
Order By: Relevance
“…For instance, in another study, there was no signifi cant diff erence between the groups in the one-leg standing test with eyes open; however, when performing the same test with eyes closed, the duration of standing was markedly shorter in the hearing-impaired group (Nakajima et al, 2012). When hearing impairment occurs, other sensory perceptions work to recompense the defi cit (Nakajima et al, 2012;Siegel, Marchetti, & Tecklin, 1991). Likewise, in another study conducted by using the one-leg-standing test with eyes closed, hearing-impaired individuals were found to be particularly weaker in balance (Tan et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, in another study, there was no signifi cant diff erence between the groups in the one-leg standing test with eyes open; however, when performing the same test with eyes closed, the duration of standing was markedly shorter in the hearing-impaired group (Nakajima et al, 2012). When hearing impairment occurs, other sensory perceptions work to recompense the defi cit (Nakajima et al, 2012;Siegel, Marchetti, & Tecklin, 1991). Likewise, in another study conducted by using the one-leg-standing test with eyes closed, hearing-impaired individuals were found to be particularly weaker in balance (Tan et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that postural development in PD children is delayed progressively. In addition, other studies have shown that delayed postural development in children with hearing impairment persists but does not worsen (Brunt, and Broadhead 1982;Carlson 1972;Siegel, Marchetti, and Tecklin 1991). Carlson (1972) assessed PD children aged 5-10 years using the Brace Motor Ability Test, and found that the motor development of these children adaptively improved up to 7 years of age and then plateaued.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, impairment or absence of the labyrinthine righting reflex caused by vestibular dysfunction leads to a delay in gross motor and balance functions in children (Kaga 1999). Previous studies have also demonstrated that children with hearing loss show a significant increase in center-of-pressure deviation and bodysway velocity measures made during a static standing balance test, and in the balance performance measure of the subsection item of the Bruininks-Oseretsky Test of Motor Proficiency (BOTMP), when compared to normal-hearing (NH) children (Gheysen, Loots, and Van Waelvelde 2007;Rine et al 2000;Siegel, Marchetti, and Tecklin 1991;Suarez et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations